2017
DOI: 10.1016/j.breast.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of breast cancer patients with pathologic N3a lymph node stage

Abstract: The results of this study indicate that ypN3a stage, lack of expression of PR, and Ki-67 ≥ 20% negatively affect long-term outcome of patients with pN3a breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
10
1
1
Order By: Relevance
“…Recent studies investigating the clinical outcome of breast cancer patients with pathologic N3 are summarized in Table 3 [6,[8][9][10][11][12][13]. More recent, studies have reported more improved outcome 70% to 87% of 5-year OS rates and about 35% to 72% DFS rates which was resulted by more advanced standard treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies investigating the clinical outcome of breast cancer patients with pathologic N3 are summarized in Table 3 [6,[8][9][10][11][12][13]. More recent, studies have reported more improved outcome 70% to 87% of 5-year OS rates and about 35% to 72% DFS rates which was resulted by more advanced standard treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular subtype is concerned the significant prognostic factor in breast cancer. However the results in N3 breast cancer showed the diverse results [10,12,13]. Yu et al [10] reported that molecular subtype was associated with DFS only in univariate analysis not in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…reported that HER2‐positive disease and axillary metastasis were independent predictors of recurrence in patients undergoing neoadjuvant chemotherapy and then achieving a pathologic complete remission at the primary site . It is well established that a shorter DFS is associated with clinico‐pathologic factors such as tumor size of >2 cm, the involvement of lymph nodes and more advanced disease stage . In addition, it can be expected that the DFS may be prolonged in patients who achieved a greater control of the disease after receiving adjuvant chemotherapy based on a previous published study showing that it is dependent on types of treatment modalities for patients with BC .…”
Section: Discussionmentioning
confidence: 99%
“…53 It is well established that a shorter DFS is associated with clinico-pathologic factors such as tumor size of >2 cm, the involvement of lymph nodes and more advanced disease stage. 54 In addition, it can be expected that the DFS may be prolonged in patients who achieved a greater control of the disease after receiving adjuvant chemotherapy based on a previous published study showing that it is dependent on types of treatment modalities for patients with BC. 55 There is also another report showing that the use of adjuvant endocrine therapy is associated with a prolonged DFS in patients with hormone-receptor-positive BC.…”
Section: Discussionmentioning
confidence: 99%
“…While the independent predictive value of PR has been questioned [27][28][29][30][31][32], several studies have reported its role as an independent prognosticator of risk of recurrence [33][34][35][36][37][38].…”
Section: Hormone Receptorsmentioning
confidence: 99%